1995
DOI: 10.1210/en.136.12.5311
|View full text |Cite
|
Sign up to set email alerts
|

Induction of spermatogenesis by androgens in gonadotropin-deficient (hpg) mice

Abstract: Using a new experimental model for studying the hormonal induction of spermatogenesis, the hpg mouse, which has congenital functional gonadotropin deficiency due to a major deletion in the GnRH gene, we investigated the roles of testosterone (T) and dihydrotestosterone (DHT) in the initiation of spermatogenesis. Weanling homozygous hpg male mice were implanted subdermally with SILASTIC brand implants of varying lengths (0-2 cm) filled with T or DHT, using phenotypically normal (N/N or N/hpg) and untreated hpg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 0 publications
7
110
0
3
Order By: Relevance
“…Reyes et al [43] mentioned that increased testicular temperature might cause the hypoxic changes in the testicles such as increased vascularisation, decreased testicular mass, and increased interstitial space. Therefore, the observed low level of plasma-free testosterone in the ischemia only and I/R groups may be the possible cause of spermatogenic impairment, similar to Singh et al [44], who reported that testosterone was responsible for the activation and maintenance of spermatogenesis. In addition, O'Donnell et al [45] found that testosterone could help in the maturation of round and elongated spermatids.…”
Section: Discussionsupporting
confidence: 81%
“…Reyes et al [43] mentioned that increased testicular temperature might cause the hypoxic changes in the testicles such as increased vascularisation, decreased testicular mass, and increased interstitial space. Therefore, the observed low level of plasma-free testosterone in the ischemia only and I/R groups may be the possible cause of spermatogenic impairment, similar to Singh et al [44], who reported that testosterone was responsible for the activation and maintenance of spermatogenesis. In addition, O'Donnell et al [45] found that testosterone could help in the maturation of round and elongated spermatids.…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with the retained fertility reported in mature NTNKO and GFRaKO males (Widenfalk et al 2000). The preservation of spermatogenesis despite markedly reduced circulating and intratesticular androgen levels is consistent with the fact that intratesticular testosterone levels required for induction (Singh et al 1995) or maintenance (Handelsman et al 1999) of murine spermatogenesis are much lower than ambient levels prevailing in the testis or bloodstream with analogous findings reported in rats despite a significantly reduced number of seminiferous tubules and interstitial fluid testosterone levels (Zirkin et al 1989). Hence, increased androgen sensitivity in the testis of the NTNKO mice could support the maintenance of normal spermatogenesis despite markedly lowered circulating and intratesticular levels.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, RGN is underexpressed in breast and prostate cancer cases and E 2 upregulated while DHT downregulated RGN mRNA expression in MCF-7 and LNCaP cell lines, respectively (Maia et al 2009). DHT, a nonaromatizable androgen, has been shown to stimulate spermatogenesis in a similar way to testosterone (Singh et al 1995, Meachem et al 2007, O'Shaughnessy et al 2010, therefore it was used to analyze the effect of androgens on Rgn expression in rat SeT cultured ex vivo. qPCR analysis showed that DHT upregulates Rgn mRNA expression in rat cultured SeT at 24 h of exposure (Fig.…”
Section: Discussionmentioning
confidence: 99%